Diseases of Abnormal Sensitivity to Cold in Children on Psychostimulant Drugs. Issue 2 (March 2015) - Coulombe, Jéarôcme; Powell, Julie; Hatami, Afshin; Mccuaig, Catherine; Renet, Sophie; Marcoux, Danielle
Background: Oral psychostimulant (PS) drugs, the pharmacologic treatment of choice for attention-deficit/hyperactivity disorder (ADHD), have been associated with diseases of abnormal sensitivity to cold (DASC) such as Raynaud phenomenon and acrocyanosis. Objectives: In a cohort of pediatric patients with DASC, we sought to identify prevalence and clinical features of patients on PS drugs. Methods: A 6-year retrospective chart review (2005-2011) of Ste-Justine University Hospital Center DASC patients with and without exposure to PS drugs was performed. Clinical data were analyzed with descriptive statistical methods. Results: Of 43 patients with DASC, 11 (25%) were exposed to PS drugs. In this group males were overrepresented, there was no evidence of collagen vascular diseases, serologic findings were not significant and the mean duration of PS intake was of 2.5 years. DASC age of onset was similar in both exposed and nonexposed patients. The incidence of more than one DASC type was greater in teenager patients with a positive family history of autoimmune and/or collagen vascular diseases. Limitations: This study is limited by its small population size, short follow-up period and its retrospective nature. Conclusion: Physicians should be aware of PS drugs as possible triggers for DASC.